Percutaneous Treatments of Benign Bone Tumors - Koch, Guillaume; Cazzato, Roberto Luigi; Gilkison, Andrew; Caudrelier, Jean; Garnon, Julien; Gangi, Afshin (Seminars in Interventional Radiology, 2018)
Benign bone tumors consist of a wide variety of neoplasms that do not metastasize but can still cause local complications. Historical management of these tumors has included surgical treatment for lesion resection and possible mechanical stabilization. Initial percutaneous ablation techniques were described for osteoid osteoma management. The successful experience from these resulted in further percutaneous image-guided techniques being attempted, and in other benign bone tumor types. In this article, we present the most common benign bone tumors and describe the available results for the percutaneous treatment of these lesions.
Keywords: benign bone tumor; radiofrequency ablation; cryoablation; osteoid osteoma; vertebral hemangioma; interventional radiology